(untitled) (International Journal of Health, Animal Science and Food Safety, 2015)
Lead is a well-known toxic heavy metal, which can have serious public health hazards at very low levels, especially for young children. This report summarized the background information on lead as well as its applications, pollution sources, poisoning pathways, biomarkers of exposure and effect, toxicities, poisoning mechanisms, preventive actions, decontamination strategies, and detoxification methods.